Digital Work and the Platform Economy: Understanding Tasks, Skills and Capabilities in the New Era - Seppo Poutanen; Anne Kovalainen; Petri Rouvinen (United Kingdom Routledge, 2021)
"Uberization," "digitalization," "platform economy," "gig economy," and "sharing economy" are some of the buzzwords that characterize the current intense discussions about the development of the economy and work around the world, among both experts and laypersons. Immense changes in the ways goods are manufactured, business is done, work tasks are performed, education is accomplished, and so on, are clearly underway. This also means that demand for careful, first-rate social scientific analyses of the phenomena in question is rapidly growing. This edited volume gathers distinguished researchers from economics, business studies, organization studies, medicine, social psychology, occupational health, pedagogics, and sociology to put particular work in both public and private sectors and education in both academic and vocational settings at the focus of the emerging digitalized platform economy. The authors anchor their analyses and conceptual and theoretical work in distinctive empirical developments that are taking place in one of the leading countries of digitalization processes: Finland. Finnish case studies reflect general global developments and show their particular, context-related actualization in multiple ways. This double exposure enables the authors of this multi- and interdisciplinary volume to advance conceptualization and theorization of the key phenomena in digitalizing platform societies in novel, creative, and groundbreaking directions. This book will without doubt be of great value to academic researchers and students in the fields of economics, business studies, work studies, social sciences, education, technology, digitalization, platforms, occupational health, entrepreneurship, and professions.
Keywords: (MGT101) Business Organisations and Society